Art and architecture of the Middle Ages : exploring a connected world - Caskey, Jill, 1964- (Cornell University Press, 2022)
"Dismantles the religious, political, and geographic walls that have separated medieval art and architecture and treats not only western Europe but also the Byzantine Empire and the Islamicate world from ca. 200 CE to ca. 1450 CE. Includes a wide variety of art forms, from large architectural complexes to small amulets printed on paper"--